2021
DOI: 10.1007/s40142-021-00198-y
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Epigenome-Modifying Drugs in Cardiometabolic Disease

Abstract: Cardiometabolic disorders, including cardiovascular disease, obesity and type 2 diabetes are an extreme burden on the health of individuals and societies worldwide. The combination of genetic susceptibility, environmental, and lifestyle factors drive disease development. Therefore, understanding the exact molecular changes occuring in their pathogenesis brings not only insights into mechanism, but also potential novel therapeutic angles. Epigenetic changes -the mitotically heritable chemical marks or packaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 182 publications
0
2
0
Order By: Relevance
“…The epigenome consists of histone modifications as well as DNA modifications. Epigenomic readers, writers and erasers are required to precisely co-ordinate the epigenomic machinery (Figure from Berjawi & Bell [ 55 ]) …”
Section: The Epigenome Is a Co-ordinated Multi-layered Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…The epigenome consists of histone modifications as well as DNA modifications. Epigenomic readers, writers and erasers are required to precisely co-ordinate the epigenomic machinery (Figure from Berjawi & Bell [ 55 ]) …”
Section: The Epigenome Is a Co-ordinated Multi-layered Apparatusmentioning
confidence: 99%
“…This applicability of these epigenomic modifiers was made clear through the large-scale cancer sequencing projects that identified that mutations in the epigenomic machinery were frequent, as with developmental orders, with ~ 50% of human cancers possessing mutations in chromatin organisation enzymes [ 303 ]. However, modulation of the epigenome has considerable potential for non-malignant diseases as well, with potential for BETi and HDACi in vascular inflammation and atherosclerosis, respectively [ 55 ]. The wide-ranging therapeutic possibilities of H3K27 demethylase inhibitors involve KDM6A/B inhibition as an anti-inflammatory mechanism for autoimmune and inflammatory disorders, as well as an immunopathological suppressant for infectious pathogens [ 304 ].…”
Section: Therapeutic Modulation Of the Epigenome Through Epidrugsmentioning
confidence: 99%